Estudo retrospectivo da dermatite trofoalérgica canina em um Hospital Veterinário de Jaboticabal, São Paulo, Brasil - Rondelli, Mariana Cristina Hoeppner [UNESP]; De Oliveira, Michele Cristina Camargo [UNESP]; Da Silva, Flavio Lopes; Palacios Junior, Reinaldo Juan Garrido; Peixoto, Mayara Corrêa [UNESP]; Carciofi, Aulus Cavalieri [UNESP]; Tinucci-Costa, Mirela [UNESP] (FapUNIFESP (SciELO), 2015)
Cutaneous food allergy is an adverse immunological response, triggered by antigenic dietary components that may escape the digestion process and are absorbed intact through the gastrointestinal mucosa. In Brazil, there are only a few reports on cutaneous food allergy and antigenicity of food components used in pet food production. Thus, the aim of this report was to assess and describe data from medical records of canine patients diagnosed with cutaneous food allergy at a Veterinary Teaching Hospital from Jaboticabal, SP, Brazil, in order to evaluate epidemiological and clinical aspects related to this skin problem. From 2007 to 2012, 29 dogs received the diagnosis of cutaneous food allergy after an eight-week hypoallergenic elimination trial. Among them, purebred dogs were more frequent, as well as females, and their mean age was 50.4 months old. Pruritus was reported in all cases, especially in interdigital areas. In order to establish the diagnosis, most patients received home-cooked elimination diet, based on potato and lamb in approximately 80% of the cases. Besides, it was highlighted the importance of the hypoallergenic elimination diet being rigorously followed by dogs’ owners, aiming the adequate control of the clinical signs related to cutaneous food allergy.
A retrospective study of canine cutaneous food allergy at a veterinary teaching hospital from Jaboticabal, São Paulo, Brazil
Keywords: Dogs; Food allergy; Hypoallergenic diet